The Mutual Gains Enterprise: Forging a Winning Partnership among Labor, Management, and Government - Perline, Martin M. (Relations industrielles / Industrial Relations, 1995)
The article reviews the book, "The Mutual Gains Enterprise: Forging a Winning Partnership among Labor, Management, and Government," by Thomas A. Kochnan and Paul Osterman.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Human resource management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Working conditions